Answer:
The angles of a parallelogram are 135°-45°-135°-45°
Step-by-step explanation:
we know that
In a parallelogram opposites angles are congruent and consecutive angles are supplementary
Remember that
The sum of a exterior angle and its interior angle is equal to 180 degrees
Let
x ----> the measure of one interior angle of parallelogram
y ----> the measure of the other interior angle of parallelogram
we have that
solve for x
![\frac{4}{3}x=180^o\\\\x=(180^o)3/4\\\\x=135^o](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7Dx%3D180%5Eo%5C%5C%5C%5Cx%3D%28180%5Eo%293%2F4%5C%5C%5C%5Cx%3D135%5Eo)
<em>Find the measure of the other interior angle of parallelogram</em>
Remember that consecutive interior angles are supplementary
![x+y=180^o](https://tex.z-dn.net/?f=x%2By%3D180%5Eo)
substitute the value of x
![135^o+y=180^o](https://tex.z-dn.net/?f=135%5Eo%2By%3D180%5Eo)
solve for y
![y=45^o](https://tex.z-dn.net/?f=y%3D45%5Eo)
therefore
The angles of a parallelogram are 135°-45°-135°-45°
Answer:
(3, -6)
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality<u>
</u>
<u>Algebra I</u>
- Coordinates (x, y)
- Terms/Coefficients
- Solving systems of equations using substitution/elimination
Step-by-step explanation:
<u>Step 1: Define Systems</u>
y = 4x - 18
y = -5x + 9
<u>Step 2: Solve for </u><em><u>x</u></em>
<em>Substitution</em>
- Substitute in <em>y</em> [2nd Equation]: 4x - 18 = -5x + 9
- [Addition Property of Equality] Add 5x on both sides: 9x - 18 = 9
- [Addition Property of Equality] Add 18 on both sides: 9x = 27
- [Division Property of Equality] Divide 9 on both sides: x = 3
<u>Step 3: Solve for </u><em><u>y</u></em>
- Substitute in <em>x</em> [1st Equation]: y = 4(3) - 18
- Multiply: y = 12 - 18
- Subtract: y = -6
Use the elimination process
The population of California is 3.88 x 10^7 - 5.84 x 10^5 = 3.82 x 10^7 more than the population of Wyoming. Alternatively the population of California is 3.88 x 10^7 / 5.84 x 10^5 = 66 times the population of Wyoming.
Thank you for posting your question here at brainly. I hope the answer will help you. Feel free to ask more questions.
E = 3(6^2)
E = 3(36)
And your answer is E = 108 :)